Digital Audit Practices and Procedural Compliance as Determinants of Audit Quality in the Public Sector - Muhammad Rusdi Salim; Evada Dewata; Devi Febrianti (JURNAL ECONOMINA, 2026)
This research investigates how remote audit, e-audit, and standard operating procedures (SOPs) affect audit quality at BPK RI Representative Office of South Sumatra Province. Employing a quantitative methodology, primary data were gathered from 32 auditors through a saturated sampling approach. Data collection achieved a response rate of 80%, utilizing structured questionnaires with a five-point Likert measurement scale. The collected data were analyzed using multiple linear regression with IBM SPSS Statistics version 26. The findings indicate that remote audit does not have a significant effect on audit quality. In contrast, e-audit and standard operating procedures have positive and significant effects on audit quality. Furthermore, the simultaneous implementation of remote audit, e-audit, and SOPs significantly influences audit quality, explaining 41.9% of its variation. Among the independent variables, e-audit emerged as the most dominant factor affecting audit quality. These results suggest that the effective utilization of digital audit systems and consistent adherence to established procedures can improve audit accuracy, efficiency, and reliability. Therefore, strengthening e-audit implementation and ensuring compliance with standard operating procedures are essential strategies for enhancing audit quality in the public sector.